THE CHALLENGE OF UNDERSTANDING NATURE IN MILTON SANTOS’S WORK (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
It is intended, in this article, to discuss how Milton Santos theorizes the concept of Nature and how it is integrated to the spatial totality. Two questions guide the text: “What is the place of nature in historic game of superstructure and infrastructure, in the economic and social formation?” And “Is it possible to know the nature fully and rationally in the current technical-scientific-informational period?” The premise is that Nature is a constant concern to Santos, but its meaning in the totality is not immediately visible, and should therefore be deepened in his work. The idea of this article is to contribute to the reflection about the ways of Milton Santos, without reaching definite results, but contribute to new thinkings.